Distancing or drawing together: Sexism and organisational tolerance of sexism impact women's social relationships at work. (7th July 2020) - Ciftci, Esma Esen; Barreto, Manuela; Doyle, David Matthew; van Breen, Jolien; Darden, Safi
Abstract: This article examines the role of organisational climate in women's social responses to sexism at work. We argue that after experiences of sexism, women "draw together" with other women when they perceive that the organisational climate is intolerant of sexism. We assess the role of organisational climate at three levels: peer‐, manager‐, and policy‐level. We conducted a correlational study ( N study1  = 405) and two experimental studies ( N study2  = 377, N study3  = 391), in which we examined women's experiences of sexism at work (measured in Study 1; manipulated in Studies 2 and 3). We also measured perceived tolerance of sexism at the peer‐, manager‐ and policy‐level in all studies. The main DVs were women's workplace friendships with other women in Studies 1 and 2, and closeness to female co‐workers in Study 3. Results showed that perceived tolerance of sexism from peers was especially important in shaping women's social relationships following experiences of sexism; tolerance from managers or at the policy level had less consistent effects. Specifically, experiences with sexism were positively associated with female participants' reported friendship (Studies 1 and 2) and closeness (Study 3) with their female colleagues, but only when peers were perceived not to tolerate sexism. When peers were perceived to tolerate sexism, female participants did not respond to sexism by drawing together.